Energy-Based Seismic Design Method for EBFs Based on Hysteretic Energy Spectra and Accumulated Ductility Ratio Spectra - Cuiling Ma (Advances in Civil Engineering)
In the case of far field earthquakes, structural failure often results from accumulated damage caused by cyclic effects and gradual accumulation of energy. This paper proposes an energy-based seismic design method for steel eccentrically braced frames (EBFs) with two shear links at every story according to the energy balance concept. The proposed method is theoretically supported by hysteretic energy spectra and accumulated ductility ratio spectra according to the Chinese soil classification. Furthermore, the method can be used to clarify the relationship between cumulative hysteretic energy and one-way pushover energy. For developing the method, it is assumed that all the hysteretic energy is dissipated by the shear links, column bases, and beam ends of the frames at both sides. Therefore, the parts outside the links, including beam segments, braces, and columns, are specially designed to perform elastically during an earthquake. Furthermore, a V-scheme steel EBF with ten stories and three spans is designed. The seismic performances of the designed structure, such as story drift and energy dissipation, are evaluated by nonlinear static analysis and time-history analysis. Finally, the reliability and accuracy of the proposed seismic design method are validated.